A review of anammox-based nitrogen removal technology: From microbial diversity to engineering applications - Ren, Zhi-Qi; Wang, Hao; Zhang, Li-Ge; Du, Xue-Ning; Huang, Bao-Cheng; Jin, Ren-Cun (Bioresource technology, 2022)
The anaerobic ammonium oxidation (anammox) process has the advantages of high efficiency and low energy consumption, so it has broad application prospects in biological denitrification of wastewater. However, the application of anammox technology to existing wastewater treatment is still challenging. The main problems are the insufficient supply of nitrite and the susceptibility of anammox bacteria to environmental factors. In this paper, from the perspective of the diversity of anammox bacteria, the habitats and characteristics of anammox bacteria of different genera were compared. At the same time, laboratory research and engineering applications of anammox technology in treating wastewater from different sources were reviewed, and the progress of and obstacles to the practical application of anammox technology were clarified. Finally, a focus for future research was proposed to intensively study the water quality barrier factors of anammox and its regulation strategies. Meanwhile, a combined process was developed and optimized on this basis.The anaerobic ammonium oxidation (anammox) process has the advantages of high efficiency and low energy consumption, so it has broad application prospects in biological denitrification of wastewater. However, the application of anammox technology to existing wastewater treatment is still challenging. The main problems are the insufficient supply of nitrite and the susceptibility of anammox bacteria to environmental factors. In this paper, from the perspective of the diversity of anammox bacteria, the habitats and characteristics of anammox bacteria of different genera were compared. At the same time, laboratory research and engineering applications of anammox technology in treating wastewater from different sources were reviewed, and the progress of and obstacles to the practical application of anammox technology were clarified. Finally, a focus for future research was proposed to intensively study the water quality barrier factors of anammox and its regulation strategies. Meanwhile, a combined process was developed and optimized on this basis.